WAYS TO SOLVE EMPLOYMENT PROBLEMS IN THE REGION THROUGH ENTREPRENEURSHIP - Ergasheva Nasiba , Rakhmatullaevna; Barotov Komiljon , Farkhad ugli (THE INNOVATION ECONOMY, 2025)
This scientific article is devoted to the study of the theoretical and methodological foundations of increasing the income of the population based on the aggravation of employment problems in Uzbekistan and the role of entrepreneurship in their elimination. The study examines the importance of developing small and mediumsized businesses, creating new jobs, implementing innovative technologies, and improving economic infrastructure in ensuring regional Economic growth and social stability. The article also analyzes effective methods aimed at strengthening cooperation between the state and the private sector, attracting financial resources, and optimizing Economic policy.